The Characterization of Liquefied Petroleum Gas (LPG) Using a Modified Bunsen Burner - Bader A Alfarraj; Ahmed A. Al-Harbi; Saud A. Binjuwair; Abdullah Alkhedhair (Journal of Combustion)
The equivalence ratio ranges were found between 22.77 and 42.93 for the Saudi LPG/air mixture using a traditional Bunsen burner. An operation problem was found with a traditional Bunsen burner for the Saudi LPG/air mixture, especially in a lean mixture. Therefore, a Bunsen burner was successfully modified to overcome the limits of operation with different mixtures of Saudi LPG/air and a stable flame was obtained. The equivalence ratio ranges were found between 0.68 and 1.30 using the modified Bunsen burner. A premixed flame was used for the modified Bunsen burner. A MATLAB algorithm was successfully applied to flame image processing and measurement of laminar burning velocity. The laminar burning velocity was determined to be approximately 35 ± 0.91 cm/s under stoichiometric conditions using the modified Bunsen burner for the Saudi LPG/air mixture. The half-cone angle of the flame was found to be 16.20 ± 0.76°. The minimum flame height was observed to be 21.50 ± 0.22 mm above the Bunsen burner exit.